Ocorrência polimetálica em Gossan e brechas hidrotermais no grupo Roosevelt, na região de Boa Vista do Pacarana, estado de Rondônia: resultados preliminares - PROVENZANO, Carlos Augusto Silva (2024)
Preliminary data from an occurrence of sulfide bearing breccia and gossan are presented here. Suchoccurrence was found during the 1:100.000 scale geological mapping carried out by the Geological Survey of Brazil – SGB/CPRM, in the region of Boa Vista do Pacarana - Espigão d'Oeste, state of Rondônia. The host rock is an acid metavolcanic paleoproterozoic rock of the Roosevelt Group, southwest Amazon Craton. It is already known from previous works in Mato Grosso state that metal deposits can be formed when rocks from the Roosevelt Group are subjected to hydrothermal alteration related to VHMS system and by late heating and remobilization of mineralization by influence of fluids derived from intrusion of calymmian magmatic rocks. Could this environment be alson occurring in Rondônia state? That is a question to be answered in time with further studies. Here we present initial indications from field, petrographic and chemical data.